PSYHOPHYSIOLOGICAL AND PSYCHOLOGICAL DIFFERENTIAL DIAGNOSTICS OF THE IDENTITY STRESS SUBJECT - A. Yu. Kivorkova; O. A. Ahverdova; N. N. Voloskova (Бюллетень сибирской медицины, 2013)
The article is considering psyhophysiological and psychological differential diagnostics of the identity stress subject. Psyhophysiological diagnostics using biofeedback technology is presented with software complex “BOSLAB”. Psychological diagnostics is presented in constitutional-psychotypological continuum of the personality.